Measuring the surrogacy potential of charismatic megafauna species across taxonomic, phylogenetic and functional diversity on a megadiverse island. Issue 5 (12th March 2019) - Sibarani, Marsya C.; Di Marco, Moreno; Rondinini, Carlo; Kark, Salit
Abstract: Conservation organisations and governments often use charismatic megafauna as surrogates to represent broader biodiversity. While these species are primarily selected as "flagships" for marketing campaigns, it is important to evaluate their surrogacy potential, i.e. the extent to which their protection benefits other biodiversity elements. Four charismatic megafauna species are used as surrogates in the megadiverse island of Sumatra: the Sumatran tiger Panthera tigris sumatrae, Sumatran elephant Elephas maximus sumatranus, Sumatran orangutan Pongo abelii and Sumatran rhinoceros Dicerorhinus sumatrensis . We examined how well each of these species performed in representing the distribution of all co‐occurring terrestrial mammal species on the island, and the priority areas for the conservation of three facets of mammalian biodiversity (taxonomic, phylogenetic and functional). We used habitat suitability models to represent the distribution of 184 terrestrial mammal species, 160 phylogenetic groups and 74 functional trait groups. We then identified priority conservation areas using the spatial prioritisation software Zonation. We found that the habitat overlap between each of the four charismatic species and the other mammal species varied, ranging from a mean of 52% ( SD = 27%) for the tiger to 2% ( SD = 2%) for the rhino. Combining the four species together improved the representation levels only marginally compared to using the tiger only. Among the four charismatic megafauna species, the extent of suitable habitat of Sumatran tiger covered the highest proportion of priority conservation areas. The Sumatran tiger also outperformed most of other mammal species with similar range sizes. We found that some of the top‐ranked conservation areas for taxonomic (28%), phylogenetic (8%) and functional diversity (19%) did not overlap with any of the charismatic species' suitable habitat. Synthesis and applications . Wide‐ranging charismatic species can represent broader mammalian biodiversity, but they may miss some key areas with high biodiversity importance. We suggest that a combination of systematic spatial prioritisation and surrogacy analyses are important in order to determine the allocation of conservation resources in biodiversity‐rich areas such as Sumatra, where an expansion of the protected area network is required. Abstract : Wide‐ranging charismatic species can represent broader mammalian biodiversity, but they may miss some key areas with high biodiversity importance. We suggest that a combination of systematic spatial prioritisation and surrogacy analyses are important in order to determine the allocation of conservation resources in biodiversity‐rich areas such as Sumatra, where an expansion of the protected area network is required. Foreign Language AbstractAbstrak: Organisasi konservasi dan pemerintah seringkali menggunakan megafauna karismatik sebagai spesies pengganti untuk merepresentasikan biodiversitas yang lebih luas. Walaupun spesies pengganti biasanya memilik peran utama sebagai " flagship " untuk kampanye, penting juga untuk mengetahui apakah perlindungan spesies tersebut dapat memberikan keuntungan bagi aspek biodiversitas lainnya. Empat megafauna karismatik digunakan sebagai spesies pengganti di Pulau Sumatera, yaitu harimau sumatera Panthera tigris sumatrae, gajah sumatera Elephas maximus sumatranus, orangutan sumatera Pongo abelii dan badak sumatera Dicerorhinus sumatrensis . Kami mengevaluasi bagaimana keempat spesies tersebut merepresentasikan distribusi spesies mamalia terestrial lainnya di Sumatera dan area prioritas untuk konservasi tiga aspek keanekaragaman hayati (taksonomik, filogenetik, dan fungsional). Kami menggunakan pemodelan kesesuaian habitat untuk merepresentasikan distribusi 184 spesies mamalia terestrial, 160 kelompok filogenetik, dan 74 kelompok karakteristik fungsional. Kami kemudian mengidentifikasi area konservasi prioritas menggunakan perangkat lunak Zonation. Tumpang‐tindih habitat di antara keempat spesies karismatik dan spesies mamalia lainnya bervariasi, berkisar dari rerata 52% ( SD = 27%) untuk harimau hingga 2% ( SD = 2%) untuk badak. Menggabungkan distribusi keempat spesies hanya sedikit meningkatkan tumpang‐tindih habitat dibandingkan jika hanya menggunakan harimau. Di antara keempat spesies karismatik, habitat yang sesuai bagi harimau sumatera melingkupi area konservasi prioritas dengan proporsi tertinggi. Harimau sumatera juga mengungguli sebagian besar mamalia lain yang memiliki luas habitat yang serupa. Beberapa area konservasi prioritas untuk keanekaragaman taksonomik (28%), filogenetik (8%), dan fungsional (19%) tidak bertumpang‐tindih dengan habitat spesies karismatik mana pun. Sintesis dan aplikasi . Spesies karismatik dengan distribusi yang luas dapat merepresentasikan keanekaragaman mamalia, tetapi dapat juga melewatkan beberapa area yang penting untuk konservasi biodiversitas. Kombinasi antara analisis spasial untuk menentukan prioritas konservasi dan analisis surogasi merupakan hal yang penting untuk menentukan alokasi sumber daya konservasi di area yang kaya akan biodiversitas, seperti Sumatera, di mana perluasan kawasan konservasi diperlukan.